تأثير المستخلصات المائية والبقايا الجافة لبعض نباتات العائلة الصليبية في إنبات ونمو بعض النباتات - طباش سمير; المغربي صباح; حوش ماري (Latakia University Journal -Biological Sciences Series, 2019)
جرت دراسة تأثير استخدام بقايا النباتات التابعة للعائلة الصليبية (الكرنب,الملفوف,الفجل)في إنبات ونمو بعض النباتات ( القمح, الفجل, الرشاد, الهندباء) حيث استخدمت المستخلص المائي والمسحوق الجاف لها بتركيز: 1.25 ,2.5 ,5 % ، وتبين أن استخدام المستخلص المائي للملفوف بالتركيز 5% كان الأكثر تأثيرا في النباتات الأربعة المستخدمة وبلغت نسبة الإنبات:80 ,76.7 ,53.3 ,80 %,وطول السويقة:5.45cm,4.1 ,4.7,0.87,وطول الجذ ير: cm 3.12 ,1.38 ,1.05 ,0.33 على التوالي . وكان استخدام المسحوق الجاف للملفوف بتركيز5% الأكثر تأثيرا على النباتات حيث بلغت أطوال النباتات الأربعة المستخدمة في الاختبارات:23 cm, 10.1, 7.62, 2.28 على التوالي ، كما كان لاستخدام المسحوق الجاف للكرنب وللملفوف بالتركيز5% التأثير الأكبر في الوزن الرطب للنباتات المعاملة. وبشكل عام نباتات الرشاد والهندباء كانت الأكثر حساسية لتأثير المستخلصات المائية والمساحيق الجافة للنباتات الصليبية المستخدمة في الاختبارات بتراكيزها الثلاثة . This study was carried out to examine the effect of some Brassicas residues (Cabage, Radish, and Kohlrabi), using water extracts and dry powder in three concentrations: 1.25, 2.5, 5% on the growth and germination of plants (Wheat, Radish, Cress, Chicory). The results revealed that cabbage extract in 5% was most effective on plants germination (80, 76.7, 53.3, 80%) in succession, and on the stem growth (5.45, 4.1, 4.7, 0.87 Cm) in succession, and on the root growth (3.12, 1.38, 1.05, 0.33 Cm) in succession . On the other hand, using cabbage dry powder in 5% affected plants growth and the lengths were (23,10.1,7.62,2.28 Cm) in succession . Also, using cabbage dry powder and kohlrabi dry powder in 5% was most effective on plants wet weight In general, cress and chicory plants were most sensitive to the effect of Brassicas water extracts and dry powder used in study.